Histone deacetylase inhibitors modulate KATP subunit transcription in HL-1 cardiomyocytes through effects on cholesterol homeostasis - Naheed eFatima; Devin C Cohen; Gauthaman eSukumar; Tristan M Sissung; James F Schooley; Mark C Haigney; William C Claycomb; Rachel T Cox; Clifton Lee Dalgard; Susan E. Bates; Thomas P Flagg (Frontiers Media S.A., 2015)
Histone deacetylase inhibitors (HDIs) are under investigation for the treatment of a number of human health problems. HDIs have proven therapeutic value in refractory cases of cutaneous T-cell lymphoma,. Electrocardiographic ST segment morphological changes associated with HDIs were observed during development. Because ST segment morphology is typically linked to changes in ATP sensitive potassium (KATP) channel activity, we tested the hypothesis that HDIs affect cardiac KATP channel subunit expression. Two different HDIs, romidepsin and trichostatin A, caused ~20 fold increase in SUR2 (Abcc9) subunit mRNA expression in HL-1 cardiomyocytes. The effect was specific for the SUR2 subunit as neither compound causes a marked change in SUR1 (Abcc8) expression. Moreover, the effect was cell specific as neither HDI markedly altered KATP subunit expression in MIN6 pancreatic β-cells. We observe significant enrichment of the H3K9Ac histone mark specifically at the SUR2 promoter consistent with the conclusion that chromatin remodeling at this locus plays a role in increasing SUR2 gene expression. Unexpectedly, however, we also discovered that HDI-dependent depletion of cellular cholesterol is required for the observed effects on SUR2 expression. Taken together, the data in the present study demonstrate that KATP subunit expression can be epigenetically regulated in cardiomyocytes, defines a role for cholesterol homeostasis in mediating epigenetic regulation and suggests a potential molecular basis for the cardiac effects of the HDIs.